2022
DOI: 10.1111/nph.18391
|View full text |Cite
|
Sign up to set email alerts
|

Field evidence for litter and self‐DNA inhibitory effects on Alnus glutinosa roots

Abstract: Summary Litter decomposition releases nutrients beneficial to plants but also induces phytotoxicity. Phytotoxicity can result from either labile allelopathic compounds or species specific and caused by conspecific DNA. Aquatic plants in flowing water generally do not suffer phytotoxicity because litter is regularly removed. In stagnant water or in litter packs an impact on root functionality can occur. So far, studies on water plant roots have been carried out in laboratory and never in field conditions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…The two types of negative plant-soil feedback considered differ in the timing of the negative soil effects within the lifespan of the tree species. Empirical studies have shown how negative plant-soil feedbacks may involve a reduced germination of seeds (possibly due to the presence of soil autotoxicity, although pathogen also may have a role), as well as reduced survival of seedlings, most likely related to the presence of soil-borne pathogens 11,12,19,24,32 . As our model framework explicitly considers the seed, seedling, and adult stages within a tree population, negative feedback through reduced seed germination and seedling survival can both be modelled (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two types of negative plant-soil feedback considered differ in the timing of the negative soil effects within the lifespan of the tree species. Empirical studies have shown how negative plant-soil feedbacks may involve a reduced germination of seeds (possibly due to the presence of soil autotoxicity, although pathogen also may have a role), as well as reduced survival of seedlings, most likely related to the presence of soil-borne pathogens 11,12,19,24,32 . As our model framework explicitly considers the seed, seedling, and adult stages within a tree population, negative feedback through reduced seed germination and seedling survival can both be modelled (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, alternative mechanisms generating negative plant-soil feedback have also been suggested. Specifically, accumulation of conspecific DNA fragments may create an auto-toxic soil environment 23 , which prevents seed germination and growth 24 . The above description points to another shortcoming of classic Lotka-Volterra type models, in that they typically do not distinguish between mechanisms acting at different times or life stages in the population(s) of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, stronger responses to self- in comparison to nonself-DNA were reported in most, although not all, of the studies that compared DNA from different sources. Even the ‘Mazzoleni-effect’ – a dosage-dependent inhibition of growth by self-DNA, but not nonself-DNA that has been described originally by the group of Stefano Mazzoleni – could subsequently be confirmed in different models, including a tree ( Alnus glutinosa ), freshwater and marine algae and the nematode, Caenorhabditis elegans ( 18 , 21 , 22 , 30 , 31 , 35 , 37 , 38 ). Differential responses to self- versus nonself-DNA are significant even when nonself-DNA from closely related genotypes (species of the same genus or ecotypes of the same species) is used ( 21 , 26 , 31 , 35 , 36 , 38 ).…”
Section: Introductionmentioning
confidence: 92%
“…phenolic and aromatic compounds of low molecular weight) that are rapidly released following the start of litter decomposition, while longer‐term autotoxicity seems to be mainly due to self‐DNA fragments (Fig. 1), which are more slowly degraded, accumulate during litter decomposition and cause severe plasmolysis in epidermal and cortical root cells (Mazzoleni et al ., 2015; Bonanomi et al ., 2022). Plants integrate soil chemical cues to optimise the timing of germination (Renne et al ., 2014) and distinguish between self and nonself organs (self/non‐self recognition), as well as between closely related and distantly related individuals (kin recognition; Mahall & Callaway, 1991; Biedrzycki et al ., 2010; Fang et al ., 2013; Wang et al ., 2021), which will likely affect the way they respond to the soil metabolome of conspecifics (including differential effects of closely vs distantly related genotypes) or heterospecifics (Cahill et al ., 2010; Cahill & McNickle, 2011; Semchenko et al ., 2014; Callaway & Li, 2020).…”
Section: A Trait‐based Framework Linking the Soil Metabolome To Plant...mentioning
confidence: 99%